International trade in the post-soviet space: Trends, threats, and prospects for the internal trade within the Eurasian Economic Union - Vera Kot; Arina Barsukova; Wadim Strielkowski; Mikhail Krivko; Luboš Smutka (Journal of Risk and Financial Management, 2023)
This paper discusses the dynamics of foreign trade in the post-Soviet space within the Eurasian Economic Union (EAEU) during the period from 2015 to 2021. Additionally, the paper analyzes export indicators in foreign and mutual trade of the EAEU member countries and diversification of the commodity structure as well as its dynamics based on the commodity concentration index for each member country. Our paper identifies the strengths and weaknesses of the EAEU, analyzes the opportunities and threats of development, and focuses on the trends and prospects. The main strengths include the institutional and legal structure of the EAEU single market, the historical, cultural, and economic proximity of the EAEU member countries, the transit potential of the territory, the high level of domestic trade, and the increasing share of ruble transactions in the trade turnover. The most significant weaknesses are the low efficiency of the institutional structure, the gap in the socio-economic level of development of the participating countries, unstable geopolitical situations in some member countries, the low level of recognition of the EAEU in the world market, economic and political conflicts of interests of the member countries, and the dependence on Western technologies in some key industries. Strategically important opportunities can be found in the creation and implementation of a long-term development strategy, diversification of trade with the Middle East and Asian countries, expansion in terms of the territorial composition, development of the institutional and legal structure as well as cooperation ties, as well as the cooperation in the field of technological innovation and financial security. Among the most significant threats were identified the outpacing growth in the share of EAEU members' trade with China, the expansion of economic and political contradictions between the EAEU member countries, and the strengthening of the positions of alternative currencies in foreign trade.
Keywords: 650; international trade; economic integration; EAEU; post-Soviet economies